Economia criativa e o consumo consciente na indústria da moda: uma análise da comunicação do movimento fashion revolution - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This Course Conclusion Paper "The Creative Economy and Consumer Consumption in the Fashion Industry: An Analysis of the Communication of the Fashion Revolution Movement". Its general goal is how a creative economy can contribute to a conscious consumption of fashion from the Movement Fashion Revolution. Since the specifics of the work are reflected on the concepts of creative economy and conscious consumption in the fashion industry, reflect on the concepts of creative economy, where it is inserted, which as forms of creative economy, together with the conscious consumption in the industry fashion, reflect on what a fashion industry is innovating and becoming aware of within the process of extracting, producing and distributing fashion. A methodology of a content analysis. The justifications for the construction of this work are for a very important study in the field of communication, seen the subject at an affordable price by the field of communication and in turn, until a "silencing" of the media, because the tragedy occurred recently and few people have access to information, because it was a tragedy that involved a large number of dead. In this sense, based on the analysis of the communicators of the Fashion Revolution Movement, one can see that it is a contributor to an awareness of a new model of consumption and where from the innovation and the creativity one can foment the consumption from a creative economic perspective.
Keywords: Comunicação; Moda; Vestuário – Indústria; Communication; CNPQ::CIENCIAS SOCIAIS APLICADAS